PEMBANGUNAN KESEJAHTERAAN SOSIAL: PEMBERDAYAAN MASYARAKAT DALAM PENDEKATAN PEKERJA SOSIAL - Maspaitella, M. J.; Rahakbauwi, Nancy (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
Empowerment constitutes one of the ways to increase society’s ability to meet their need. The goal of empowerment is to develop the potency and strength of the poor or the vulnerable group and transform them into a strong group. Effort to identify the potency of the society can be done with various approach and strategy. One of the approach or strategy is by the social work approach. Social worker as professional helper have the task to revamp the socially dysfunction society through empowerment activity.